Amyloid beta modulates astrocyte activation, glucose metabolism, and insulin pathways: implications for Alzheimer’s disease - Bentivegna, Melisa Inés María (2024)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder and the leading cause of dementia. Beyond amyloid beta (Aβ) and tau aggregation, inflammation and insulin resistance are also frequent in AD brains. Astrocytes are crucial in maintaining homeostasis and managing inflammatory responses.